β Mangostin suppress LPS-induced inflammatory response in RAW 264.7 macrophages in vitro and carrageenan-induced peritonitis in vivo - Syam, S.; Bustamam, A.; Abdullah, R.; Sukari, M.A.; Hashim, N.M.; Mohan, S.; Looi, C.Y.; Wong, W.F.; Yahayu, M.A.; Abdelwahab, S.I. (Elsevier, 2014)
Ethnopharmacological relevance The fruit hull of Garcinia mangostana Linn. has been used in traditional medicine for treatment of various inflammatory diseases. Hence, this study aims to investigate the in vitro and in vivo anti-inflammatory effect of β mangostin (βM), a major compound present in Garcinia mangostana.